IRONI PENJAGA PERDAMAIAN: KETIDAKPATUHAN STRUKTURAL DAN KEKERASAN SEKSUAL OLEH PASUKAN PERDAMAIAN PBB DI WILAYAH KONFLIK - Selvia Ranti; Dudy Heryadi; Deasy Silvya Sari (Indonesian Journal of International Relations, 2026)
This article aimed to analyze violations through sexual violence committed by United Nations (UN) peacekeeping forces in conflict areas, focusing on the causal factors and the lack of legal accountability for the perpetrators. Using a qualitative descriptive method and compliance theory, this study revealed that the non-compliance of UN peacekeeping forces with their mandate and international law occurred at the organizational structural level, caused by weak accountability mechanisms and legal immunity granted to the perpetrators. The research findings showed that sexual violence committed by UN peacekeeping forces was not merely individual violations, but demonstrated systemic organizational failure in preventing, supervising, and holding accountable for such actions. This research emphasized the need to strengthen the enforcement of international legal systems and accountability mechanisms for perpetrators of sexual violence in conflict areas to address the root causes of organizational non-compliance.